PENERAPAN POHON LITERASI WEEKDAY BERBASIS KARYA SISWA DI SD NEGERI 03 WATES - Azkadina Halipah; Siwi Utaminingtyas (Papanda Publisher, 2022)
The implementation of online learning is one of the obstacles in implementing the School Literacy Movement (GLS). One of the affected schools is SDN 3 Wates, which previously implemented the School Literacy Movement (GLS) but did not run optimally during the pandemic. The Weekday Literacy Tree Program is based on student work at SDN 3 Wates as a form of follow-up to the GLS carried out by the school by reading 15 minutes before learning. The purpose of this study was to describe how the literacy tree was implemented during a pandemic in class V students. The research method used descriptive qualitative research with class V students with 24 students, data collection techniques used observations and interviews. Based on the results of the study, the implementation of the weekday literacy tree based on student work at SDN 3 Wates showed that the implementation of the weekday literacy tree was limited face-to-face, fifth grade students were divided into two groups on different days, Monday-Friday and Tuesday-Saturday after the activity. learning in the library. On Fridays and Saturdays students collect their work by hanging on the literacy tree that has been provided in the library.